The Effectiveness of The Application of The Drill Method and the Contextual Approach of Teaching at the Right Level to Improve Mathematics Division Skills in Mathematics Class V Saoraja at UPT SPF SDNPilot PAM Makassar City - Muhammad Hamzah Muslimin; Hikmawati Usman; Ika Ayuvia Johan (Sains Global Institut, Indonesia, 2026)
Mathematical division skills are a challenge for students because this concept requires in-depth understanding and basic operational skills. Low learning outcomes in division material indicate the need for a more adaptive and contextual approach. This study aims to improve students' division skills through the application of the drill method and a contextual approach based on Teaching at the Right Level (TaRL), which adapts learning materials to students' ability levels. This study is a classroom action research (CAR) in three cycles. Each cycle involves four stages: planning, action, observation, and reflection. The drill method is used to strengthen calculation skills, while the contextual approach is applied to help students understand the concept of division through real situations. Data were collected through a mathematical understanding test, observation of the learning process, and interviews with students and teachers. The results showed that the TaRL method significantly improved students' division understanding. At the end of the third cycle, the average student test score increased by 20% compared to the initial test, with more than 90% of students achieving the Minimum Completion Criteria (KKM). In addition, students became more active and confident in solving division problems. Based on these findings, it is concluded that the drill method combined with a TaRL-based contextual approach is effective in improving the mathematical division skills of fifth-grade students and provides implications for the development of adaptive and relevant mathematics learning strategies.